Melatonin improves oxidative organ damage in a rat model of thermal injury - YEGEN, BERRAK; ŞENER, GÖKSEL (My University, 2002)
Animal models of burn injury indicate oxygen radicals as causative agents in the local wound response, as well as in the development of burn shock and distant organ injury. This study was designed to determine the possible protective effect of melatonin treatment against oxidative damage in the liver, lung and intestine induced by burn injury. Under ether anaesthesia, the shaved dorsum of rats was exposed to a 90 degrees C bath for 10s to induce burn injury. Rats were decapitated either 3 or 24h after burn injury. Melatonin was administered i.p. immediately after burn injury. In the 24h burn group, melatonin injections were repeated for two more occasions. In the sham group the same protocol was applied except that the dorsum was dipped in a 25 degrees C water bath for 10s. Liver, lung and intestine tissues were taken for the determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and protein oxidation (PO). Severe skin scald injury (30% of total body surface area) caused a significant decrease in GSH level, significant increases in MDA and PO levels, and MPO activity at postburn 3 and 24h. Treatment of rats with melatonin (10mg/kg) significantly elevated the reduced GSH levels while it decreased MDA and PO levels as well as MPO activity.
Keywords: Female; Animals; Male; Rats; Disease Models, Animal; Melatonin; Rats, Wistar; Time Factors; Oxidative Stress; Liver; Free Radical Scavengers; Intestinal Mucosa; Burns; Lung; Intestines; Lung Injury